L’apport des théories du design aux game studies : nouvelles perspectives en design de jeux vidéo - Chiapello, Laureline (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2015)
At a time when the video game industry is booming in Canada and game studies departments begin to emerge in universities, this article assesses the evolution of video game design theories. These can be considered as the combination of two worlds, design theories and video game studies, a union that seems largely under-examined. Using a theoretical model drawn from design theory, namely “the eclipse of the object,” this article reveals similarities between design and video game design theories. It argues that the parallels that can be drawn between these theories constitute the basis for a shared theoretical outlook. Building on this commonality, this paper concludes with some suggestions concerning research, pedagogy, and the video gaming industry that aim at unifying these two domains.